PENGARUH PENGETAHUAN WAJIB PAJAK, SANKSI PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KABUPATEN SUKOHARJO - Khasanah, Winda Nur; Harimurti, Fadjar; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
Tax is a taxpayer's contribution owed by an individual or entity that iscoercive based on statutory regulations, by not getting direct compensation but isused to finance state needs which are expected to have an effect on increasingincome and community welfare. The purpose of this study was to determine (1)The effect of taxpayer knowledge on PKB taxpayer compliance (2) The effect oftax sanctions on PKB taxpayer compliance, (3) The effect of taxpayer awarenesson PKB taxpayer compliance. This study uses primary data in the form of aquestionnaire given to taxpayer respondents at SAMSAT Sukoharjo Regency. Thepopulation in this study was 230,673 taxpayers in Sukoharjo district. Thesampling technique in this study using accidental sampling method. The dataanalysis technique used in this research is descriptive analysis, instrument test,classical assumption test, multiple linear regression analysis, coefficient ofdetermination test, t test and F test.The results of t count 3.230 with p-value 0.002 <0.05 means that there is asignificant effect. taxpayer knowledge (X1) on taxpayer compliance (Y). Theresult of t count 1.318 with p-value 0.191> 0.05 means that there is no significanteffect of tax sanctions (X2) on taxpayer compliance (Y) and the result of t count1.201 with p-value 0.233> 0.05 means there is no significant effect. significantawareness of taxpayers (X3) on taxpayer compliance (Y). (Y) Results of F test5.222 with a p-value of 0.002 <0.05, which means simultaneously the taxknowledge variable (X1), tax sanctions (X2) awareness tax (X3) The test ofdetermination shows the value of Adjusted R Square 0.113. It can be concludedthat the taxpayer stress variable can be explained by the three independentvariables, namely tax knowledge, tax sanctions and taxpayer awareness becauseAdjusted R Square 11.3% the remaining (100% -11.3% = 88.7%) explained byreasons other than the model.